Penerapan Pendampingan Perilaku Menabung di Bank Syariah dalam Mencegah Sikap Konsumtif - Ismawati Ismawati; Jamaluddin Jamaluddin; Samsul Samsul (Al-Azhar Journal of Islamic Economics, 2022)
This study aims to determine the application of education assistance on saving behavior that is attractive as well as to prevent and find solutions to the consumptive attitudes of elementary school students in Makassar city.  This study uses the qualitative research type.  The type of data used in this research are subject data and object data, the data is obtained from interviews with informants and documentary data.  The results of this study indicate that the steps taken in order to assist education on saving behavior are attractive to elementary school students so that they like to save, namely: the preparation stage, the implementation stage, the activity process, and the evaluation. Meanwhile, efforts to prevent and find solutions to the consumptive attitudes of elementary school students in Makassar is to provide education and understanding of how important it is to instill a simple lifestyle for elementary school children in order to be able to determine their needs rather than their desires, therefore the role of parents and also teachers are very important in that effort.